POLA PERENCANAAN PETERNAK PADA USAHA PETERNAKAN SAPI POTONG DI KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Tomatala, Andre; Tomatala, George S. J.; Matatula, Michel J. (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aims to analyze the planning patterns of livestock breeders in beef cattle farming businesses and to determine the facilitating and inhibiting factors that influence the planning patterns of livestock breeders in beef cattle farming businesses in Kairatu District, West Seram Regency. Primary data collection techniques used interview techniques and observations of respondents guided by questionnaires while secondary data were obtained from agency reports related to research results and other references related to this study. Then, the sampling technique used a purposive sampling method. Data analysis used in this study was quantitative descriptive analysis and T-test. The results of this study indicate that respondents' answers regarding livestock breeder planning patterns in Kairatu District were more dominant in answering no in the management of seed selection, fattening systems, provision of more cages and disease prevention and control while respondents who answered yes were more in the variable of feeding. Based on the results of the partial test (T), it shows that the variables that have a significant influence on livestock farmer planning patterns are the infrastructure and resource variables (X1) and limited capital (X2.1), while the variables that do not have a significant influence on livestock farmer planning patterns are the variables of limited seed sources (X2.2) and limited access to information/technology (X2.3).